2022
DOI: 10.3748/wjg.v28.i41.5968
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of patients with combined hepatocellular-cholangiocarcinoma after radical resection: A retrospective multicenter cohort study

Abstract: BACKGROUND Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a form of rare primary liver cancer that combines intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma. AIM To investigate overall survival (OS) and recurrence-free survival (RFS) after radical resection in patients with cHCC-CCA, and the clinicopathological factors affecting prognosis in two center hospitals of China. METHODS We reviewed consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To address this, the Nomogram incorporating multiple risk factors was developed to provide improved risk stratification and survival prediction. 25 , 26 In this study, risk factors included in the Nomogram were identified by multivariate analysis. All the factors included in the Nomogram are clinical variables, facilitating its further adoption in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, the Nomogram incorporating multiple risk factors was developed to provide improved risk stratification and survival prediction. 25 , 26 In this study, risk factors included in the Nomogram were identified by multivariate analysis. All the factors included in the Nomogram are clinical variables, facilitating its further adoption in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients who undergo resection for cHCC-CCA has been reported to vary across different studies, as shown in Table 1. 16,[45][46][47][48][49][50][51][52][53] Prognostic factors after cHCC-CCA resection include tumor diameter >5 cm, intrahepatic metastases, lymph node metastases, multifocality, vascular invasion, high levels of CA 19-9, incomplete capsule formation, and a resection margin of <2 cm. 15,54 One study conducted using data from the Surveillance, Epidemiology, and End Results Program (SEER) database found that liver transplantation (LT) did not provide any survival benefit compared with minor or major hepatectomy in 465 patients with cHCC-CCA.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…While surgical treatment is crucial to improving long-term prognosis of the aggressive malignancy, approximately half of the patients will experience early disease recurrence [47,48], thus reflecting a high demand for further treatment development.…”
Section: Systemic and Locoregional Treatment Approaches For Chcc-cc: ...mentioning
confidence: 99%